Family and friends influences on cigarette smoking tendency among the dormitories students of Golestan University of Medical Sciences in North of Iran - Mahdieh Shojaa; Mehrdad Aghaie; Leila Jouybari; Mostafa Qorbani; Akram Sanagoo (Al Ameen Medical College, 2014)
Introduction: Cigarette smoking leads to harmful physical and emotional disorder. Since the family atmosphere plays an important role on nurture of children, our study was done to study perspectives of the students about the family and friends influence on cigarette smoking. Material & Methods: A cross-sectional analytical study was conducted among the residents in dormitories in Golestan University of Medical Sciences which is located in Gorgan, North of Iran in 2010. The sample size consisted all of the dormitories' students. The data was gathered using a valid and reliable questionnaire and was analyzed by SPSS software and statistical tests including Chi-square, Logistic regression and Independent t-test. Results: Of 669 students, 538 of them filled out the questionnaires completely. 6.1% of them were smoker and 83.5% of them had experiences of cigarette smoking. The most important reason for the smoking tendency was "having a smoker friend". There were significant relationships among smoking with "age, gender, ethnicity, year of education, smoker mother and smoker friend" (P<0.05). Smoker mother (OR: 8.26, CI:1.97-34.68) and smoker friend (OR:4.21, CI:1.83-9.67) increased the chance of cigarette smoking tendency of the students. Conclusion: Cigarette smoking was more common among the students who have close smoker friends. It seems that enhance of public awareness about detrimental effects of smoking is needed.